Health measures of Eeyouch (Cree) who are eligible to participate in the on-the-land Income Security Program in Eeyou Istchee (northern Quebec, Canada) - Robert J. Moriarity; Aleksandra M. Zuk; Eric N. Liberda; Leonard J. S. Tsuji (BMC, 2021)
Abstract Background Participation in on-the-land programs that encourage traditional cultural activities may improve health and well-being. The Income Security Program (ISP) − a financial incentive-based on-the-land program − for Eeyouch (Cree) hunters and trappers in Eeyou Istchee was created as a result of the 1975 James Bay and Northern Quebec Agreement to help mitigate the effects of hydroelectric development on the Cree people of northern Quebec, Canada. Beyond the ISP's financial incentives, little is known about the health measures of those who are eligible to participate in the ISP (i.e. spent ≥120 days on-the-land during the previous year). Therefore, this paper's objective was to assess the health measures of northern Quebec Cree, who were eligible for participation in the ISP. Methods Using participant data (n = 545) compiled from the Nituuchischaayihtitaau Aschii Multi-Community Environment-and-Health Study, we assessed 13 different health measures in generalized linear models with the independent variable being the eligibility to participate in the ISP. Results Participants in the present study who were eligible for the ISP had significantly higher levels of vigorous and moderate activity per week, and higher concentrations of omega-3 polyunsaturated fatty acids in the blood compared to those ineligible for the ISP (i.e. spent ≤119 days on-the-land during the previous year). Encouragingly, following model adjustment for age and sex, participants eligible for the ISP did not have higher blood concentrations of mercury than those who were not eligible for the ISP. Conclusions Our results suggest that the participants eligible for participation in the ISP are likely to be healthier than those who are ineligible to participate − and are promising for on-the-land programs for Indigenous peoples beyond a financial incentive − with no apparent higher risk of increasing contaminant body burden through traditional on-the-land-activities (e.g. fish consumption).